Amino Acid-Modulated Chirality Evolution and Highly Enantioselective Chiral Nanogap-Enhanced Raman Scattering - Kumar, Panangattukara Prabhakaran Praveen; Kim, Myung-Ki; Lim, Dong-Kwon (John Wiley and Sons Inc., 2023)
Controlling the growth and selection of chiral inducers is crucial for the generation of chiral inorganic structures as observed in nature. Herein, the plasmonic chirality evolution from the Au cube seed under the presence of L -or D-amino acid as a chiral inducer is reported. The 432 Helicoid I structure is obtained using tryptophan (Trp), identical to the result with cysteine (Cys). The use of tyrosine (Tyr) produced a Helicoid IV-type structure. However, no distinctive chiral structures can be obtained using phenylalanine (Phe), valine (Val) and leucine (Leu), which indicates the critical role of amino acids in chirality evolution. In particular, Trp-Helicoid I nanoparticles (NPs) showed excellent enantioselective response toward L-or D-Cys in the colorimetric assay and Raman analysis in the presence of Trp. Furthermore, the chiroptical property with a nanogap of 23.78 +/- 0.82 nm in the Helicoid I structure further expands its applications for highly sensitive and quantitative chiral analysis for small molecules such as R/S-epichlorohydrin (ECH), R/S-limonene (LM), and R/S-2-butanol (BuOH) using a non-polarized light source. The finding of amino acid-dependent chirality evolution can widen the current understanding of chirality evolution in nature, and the use of helicoid structures with nanogaps incorporated with surface-enhanced Raman scattering (SERS) can open a new avenue for chiral spectroscopic analysis.